Fibroadenoma and Phyllodes Tumor: Similarities and Differences – A Review - Costa, R; Estrada, T; Faria, C; Sousa, V; Agapito, P (Citotech Online - Case Review, 2020)
Fibroadenoma and phyllodes tumor are the two main prototypes of breast fibroepithelial lesions. Fibroadenoma is the most common benign tumor in the female breast. The phyllodes tumor is rare and may have a benign, borderline or malignant character and in some cases may recur after excision and/or metastasize. Both neoplasms manifest clinically in the form of a breast lump. In their presence, the diagnostic approach currently adopted is the “Diagnostic Triad”, which includes clinical evaluation of the lump, imaging exams and fine needle aspiration. However, the clinical, mammographic, ultrasonographic and cytological features of fibroadenoma and phyllodes tumor may overlap. Due to the different clinical behavior and prognosis associated with these two entities, and consequently, different therapeutic approaches, their differential diagnosis is very important. Thus, it is essential to optimize existing methodologies and / or resort to other diagnostic methodologies in order to differentiate these two entities. This study was carried out with the objective of acquiring a clearer view of how the diagnosis of these two pathologies is performed, as well as highlighting the most relevant cytological and histological features, in addition to addressing other studied methodologies not yet used in the diagnosis